Peer Effects in Microenvironments: The Benefits of Homogeneous Classroom Groups - Lu, Fangwen; Anderson, Michael L. (Journal of Labor Economics, 2015)
Many believe that classroom interactions play an important role in students’ academic achievement, but there is little evidence on peer effects within subclassroom groups. We exploit random seat assignment in a Chinese middle school to estimate how the gender of neighboring students affects a student’s academic achievement. We find that being surrounded by five females rather than five males increases a female’s test scores by 0.2–0.3 standard deviations but has no significant effects on a male’s test scores. These results suggest a low-cost way to potentially improve performance within the world’s largest school system.